The effect of coenzyme Q10 on the exercise performance of cross-country skiers - Ylikoski,T.; Piirainen, J.; Hanninen, O.; Penttinen, J. (Molecular Aspects of Medicine, 1997)
Coenzyme Q10 supplementation (Bio-Qinon Pharma Nord, 90 mg/day) was studied in a double-blind cross-over study of 25 Finnish top-level cross-country skiers. With CoQ10 supplementation, all measured indexes of physical performance (AET, ANT and VO2Max) improved significantly. During verum supplementation, 94% of the athletes felt that the preparation had been beneficial in improving their performance and recovery time vs. only 33% in the placebo periods.